Gender-specific English language use of Malaysian blog authors - Syahrir Mat Ali,; Pramela Krish, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Gender-based research on the language use in blogs has its roots in the long-standing notion that men and women speak and write differently. This paper reports an empirical study on the use of English in a blog context involving Malaysian blog authors. Specifically, the study aimed to identify gender-specific English use among Malaysian blog authors and determine the differences in the language use. Using an ensemble text analysis approach, Malaysian female blog authors are more inclined towards using more verbs, adverbs and pronouns than their male counterpart, with a significant difference, while the males are inclined towards using more adjectives, nouns, determiners and prepositions/subordinating conjunctions than the females, with a significant difference. There are also differences between females and males in terms of the function words, neologisms/blog words as well as use of tag questions and adverbs initiating sentences. However, there are minimal differences between the females and males in terms of length of sentences and that the use of intensifiers, hedges, empty adjectives and emotions, thus concluding that they are not necessarily gender-specific differences. The findings can serve as useful language markers that can benefit the applied linguistics and particularly gender-based and forensic linguistic research.